A flexible cystoscopy device prototype for mechanical tissue ablation based on micro-scale hydrodynamic cavitation: Ex vivo and in vivo studies - Kestek, Ezgi; Akar, Unal; Sarraf, Seyedali Seyedmirzaei; Kanbur, Ozcan; Kirabali, Ufuk Gorkem; Sutova, Hande Eda; Ghorbani, Morteza; Kutlu, Ozlem; Uvet, Huseyin; Ekici, Asiye Isin Dogan; Ekici, Sinan; Kozalak, Gul; et al. (ELSEVIER, 2025)
Minimally invasive methods were sought for faster recovery from benign prostatic hyperplasia (BPH) and lower urinary tract (LUTS) symptoms. For this, the search for effective, low-side-effect methods for tissue ablation, particularly for managing BPH and certain bladder pathologies, has been continued to advance. In this regard, the energy released during the formation of hydrodynamic cavitation bubbles offers an alternative treatment method. In this study, we present the feasibility of the use of hydrodynamic cavitation with a flexible cystoscopy device prototype designed for the treatment of LUTS-related diseases. The developed flexible cystoscopy device prototype allows easy access to the urinary bladder through urethra with minimal pain, demonstrating its suitability as a minimally invasive approach. Precisely targeted cavitation exposure prevents prostatic capsule and bladder perforation. Moreover, an automatic actuating mechanism supports steering for real-time visual feedback. The developed device prototype was first tested on an ex vivo human bladder and then on an in vivo porcine bladder. Histopathological analyses were performed after both species were tested. For both analyses, significant tissue ablation at the targets was observed upon exposure to cavitating flows. Finally, the temperature profile on the device was obtained using a thermal camera. Accordingly, it was observed that the temperature increase during the procedure was not significant. The developed device prototype can thus realize mechanical ablation-based therapy, avoids unintended heat deposition which might appear in laser ablation and leads to fewer side effects such as uncontrolled tissue damage and low target area effectiveness that might occur in minimally invasive tissue ablation methods.
Keywords: Flexible Cystoscopy; Mechanical Tissue Ablation; Micro-Scale Hydrodynamic Cavitation; Ex vivo and in vivo Studies; Lower Urinary Tract Symptoms; Benign Prostatic Hyperplasia; URINARY-TRACT SYMPTOMS; TRANSURETHRAL NEEDLE ABLATION; SURGICAL-TREATMENT; CONVEYING FLUID; LASER-ABLATION; RESECTION; BIPOLAR; ROBOT; VAPORIZATION; Acoustics; Chemistry